The examination of the quotient of numerical semigroup with RF-matrices - Özer, Belgin; Dakkak, Fatima (Global Journal of Mathematical Analysis, 2022)
In this paper, we study quotients of a numerical semigroups with RF (Row-Factorization) matrices. We prove a formula for the Frobenious number of quotients of some families of numerical semigroups. Moreover, we examine half of the numerical semigroups, pseudo-symmetric numerical semigroups.